Exploring Treatment Strategies for Secondary Knee Osteonecrosis Using Core Decompression with Augmentation Techniques: Case Report - JSRG Saran; P Rahul; K Gavi Krishna (Journal of Orthopedics and Joint Surgery)
Aim and background: Osteonecrosis is the ischemic death of the subchondral bone due to insult to the vascular supply. The femoral head is the most common area, followed by the knee. Knee osteonecrosis is further divided into primary, secondary and postarthroscopic, based on etiology. We present a case of secondary knee osteonecrosis postcoronavirus disease 2019 (post-COVID-19) in a middle-aged woman, who initially presented with unilateral knee pain and swelling, which aggravated on performing basic household activities. Case description: A detailed history with clinical assessment revealed swelling over the knee, with painful restriction of movements and a limp while ambulating. Further radiographs and magnetic resonance imaging (MRI) revealed a reduction in the space in the medial compartment of the knee with subchondral sclerosis. A core decompression of the medial condyle of the distal femur and augmentation with synthetic bone cement and bone marrow aspirate was done, and the patient was kept non-weight bearing for 8 weeks. The patient was routinely followed up with serial radiographs and periodic MRI, along with a strict physiotherapy regimen. After the surgical intervention, there was symptomatic relief in pain, and full range of motion (ROM) at the knee joint was achieved. Conclusion: Secondary osteonecrosis of the knee with bilateral presentation is quite uncommon. The definitive management for symptomatic cases is joint preservation or replacement surgeries to achieve normal biomechanics in the knee as well as pain-free weight bearing. Core decompression with augmentation techniques gave excellent results in our patient.